Porphyrin polymers bearing N,N′-Ethylene crosslinkers as photosensitizers against bacteria - Santamarina, Sofia Carla (2022)
The appearance of microbes resistant to antibiotics requires the development of alternative therapies for the treatment of infectious diseases. In this work two polymers, PTPPF16-EDA and PZnTPPF16-EDA, were synthesized by the nucleophilic aromatic substitution of 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin and its Zn(II) complex with ethylenediamine, respectively. In these structures, the tetrapyrrolic macrocycles were N,N′-ethylene crosslinked, which gives them greater mobility. The absorption spectra of the polymers showed a bathochromic shift of the Soret band of ~10 nm with respect to the monomers. This effect was also found in the red fluorescence emission peaks. Furthermore, both polymeric materials produced singlet molecular oxygen with high quantum yields. In addition, they were capable of generating superoxide anion radicals. Photodynamic inactivation sensitized by these polymers was tested in Staphylococcus aureus and Escherichia coli bacteria. A decrease in cell viability greater than 7 log (99.9999%) was observed in S. aureus incubated with 0.5 μM photosensitizer upon 30 min of irradiation. Under these conditions, a low inactivation of E. coli (0.5 log) was found. However, when the cells were treated with KI, the elimination of the Gram-negative bacteria was achieved. Therefore, these polymeric structures are interesting antimicrobial photosensitizing materials for the inactivation of pathogens.